Prediction model of rehospitalization and mortality in heart failure patients with preserved and mildly reduced ejection fraction: the AD2NNER risk score - Stoiculescu, Flavia-Mihaela; Hădăreanu, Diana-Ruxandra; Hădăreanu, Călin-Dinu; Donoiu, Ionuț; Istrătoaie, Octavian; Raicea, Victor-Cornel; Florescu, Cristina (Frontiers in Cardiovascular Medicine, 2025)
AimsThis study aimed to identify predictors of heart failure (HF) rehospitalization and explore their association with mortality in patients with preserved (HFpEF), and mildly reduced (HFmrEF) ejection fraction, leading to the development of a multivariable risk prediction score.MethodsWe enrolled 1,022 HFpEF and HFmrEF inpatients discharged between January 2019 and May 2023. Demographic, clinical, biological, and imaging data were collected for analysis.ResultsAfter a mean follow-up of 3.5 ± 1.4 years, 308 (30.1%) patients experienced HF rehospitalization. Univariable analysis revealed several parameters associated with HF rehospitalization, including age (p < 0.001), male sex (p = 0.015), type 2 diabetes mellitus (T2DM, p = 0.016), arterial hypertension (p = 0.018), smoking (p = 0.029), NYHA class at discharge (p = 0.006), atrial fibrillation (p = 0.003), ischemic or congenital etiology (p = 0.011), serum sodium (p = 0.002), and several echocardiographic measures. Multivariate Cox regression revealed six independent predictors: age (HR = 0.98, p < 0.001), T2DM (HR = 1.31, p = 0.026), NYHA class (HR = 1.39, p = 0.010), ischemic or congenital etiology (HR = 1.33, p = 0.037), atrial fibrillation (HR = 0.65, p = 0.001), and serum sodium level (HR = 0.97, p = 0.005). These formed the AD2NNER (age, T2DM, serum natrium, NYHA class, etiology, rhythm) score, ranging from 0 to 9 points. Kaplan–Meier analysis confirmed reduced event-free survival in patients with scores ≥4 (log-rank p = 0.005). Comparative Kaplan–Meier curves using an unweighted risk count (0–6) showed less distinct stratification. Subgroup analysis revealed robust score performance in HFpEF, but not HFmrEF alone. Higher AD2NNER scores were also associated with all-cause mortality.ConclusionThe AD2NNER risk score is a simple, six-variable model that effectively predicts rehospitalization, and is also associated with mortality in patients with HFpEF and HFmrEF.